A new species of planthopper from Costa Rica in the genus Herpis (Hemiptera: Derbidae) from palms in the cloud forest - Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Helmick, Ericka E.; Bartlett, Charles R.; Bahder, Brian W. (Zootaxa, 2023)
Recent survey efforts in Costa Rica have documented many new species of planthoppers, primarily in the families Derbidae and Cixiidae, on palms. Recently, a specimen was collected sweeping palms in the Los Angeles cloud forest in Costa Rica and was identified as belonging to the genus Herpis (Derbidae). It was subsequently determined to represent a previously undescribed species. Herein, the new species, Herpis circumsoros Bahder & Bartlett sp. n. is described with supplemental molecular data for the cytochrome c oxidase subunit I (COI) gene and 18S rRNA gene to support placement of the new species in the genus Herpis.